Polyprenyl Immunostimulant in Feline Rhinotracheitis: Randomized Placebo-Controlled Experimental and Field Safety Studies - Legendre, Alfred M.; Kuritz, Tanya; Heidel, Robert Eric; Baylor, Vivian M. (Frontiers in Veterinary Science, 2017)
Feline rhinotracheitis is a ubiquitous disease caused by feline herpesvirus type 1 (FHV-1). The disease is easily transmissible and common in multi-cat environments where even vaccinated cats can develop clinical signs when exposed to the virus. Prior to the work reported here, there was no licensed treatment for the disease on the market. We hypothesized that Polyprenyl Immunostimulant, an immunomodulatory veterinary biologic, would be useful in treating feline rhinotracheitis by reducing the severity of the disease. We conducted double-blinded, randomized, placebo-controlled clinical trials to establish the efficacy of Polyprenyl Immunostimulant. Specific pathogen-free cats were administered a placebo (n = 20) or Polyprenyl Immunostimulant (n = 20) starting on the day of FHV-1 experimental challenge. Trained, masked observers applied a standardized scoring system daily in clinical examinations for 14 days after the FHV-1 challenge. The cats treated with PI had significantly lower disease severity scores over the course of the experiment compared to the cats in the placebo group (p = .05). The safety studies, including a field safety study involving 390 owned cats in 10 states, showed that Polyprenyl Immunostimulant was safe to use in cats as young as 8 weeks of age.